2011
DOI: 10.1111/j.1742-9544.2011.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Attainment of Competencies in Clinical Psychology Training: Ways Forward in the Australian Context

Abstract: Debates over models of professional training have occurred in several health disciplines, including psychology. Currently, clinical competencies form the backbone of training in clinical psychology and in standards for the accreditation of such training programs, with sample domains including ethical and legal issues, assessment, intervention, and experience with a diversity of clients across cultures and the lifespan. We review a range of models for clinical competencies that have been put forth in the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 29 publications
0
47
1
Order By: Relevance
“…Popular assessment tasks such as multiple-choice, short-answer, and essay assignments may be appropriate tasks to measure knowledge competence but be incapable of capturing progress in skills, relationship, and attitude-value competencies Pachana et al, 2011). This deficiency is probably most pronounced in the assessment of competencies in field placements.…”
Section: Measurement Of Competence and Competenciesmentioning
confidence: 99%
“…Popular assessment tasks such as multiple-choice, short-answer, and essay assignments may be appropriate tasks to measure knowledge competence but be incapable of capturing progress in skills, relationship, and attitude-value competencies Pachana et al, 2011). This deficiency is probably most pronounced in the assessment of competencies in field placements.…”
Section: Measurement Of Competence and Competenciesmentioning
confidence: 99%
“…There is general agreement among clinical psychology educators on the importance of developing and evaluating core competencies in clinical psychology training (Borden & McIlvried, 2010;Ducheny, 2010;Nelson, 2007;Pachana, Sofronoff, Scott, & Helmes, 2011). This emphasis on a competency-based model enables training programs to provide systematic assurance that their graduates are fit to practice.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Crooks, Kane, and Cohen (1996) suggested that major threats to test validity can occur at the administration stage of an assessment. Recently, Pachana et al (2011) reported on the use of a similar competency assessment process called the Multi-station Assessment Tasks (MSAT) in the clinical psychology program at the University of Queensland. Accordingly, investigations into students' feelings and attitudes following an assessment are important sources of information about the usability of an assessment.…”
Section: What Is the Osce?mentioning
confidence: 99%
“…Ahmed & Pillay, 2004). All fall within the internationally dominant scientist-practitioner model (Pachana, Sofronoff, Scott, & Helmes, 2011) but may differ in terms of their theoretical orientation. There is a greater disparity in how established some programmes are relative to others.…”
Section: Clinical Psychology Training In South Africamentioning
confidence: 99%